Theoretical Analysis on the Effect of Operation Strategies on the Environmental Performance of Micro Gas Turbine Trigeneration System in Tropical Region - K. H., Koo; M. R. R., Chand; Hassan, Ibrahim; Azizuddin, Abd Aziz; F., Basrawi (Scientific & Academic Publishing, 2015)
Trigeneration system (TGS) is a type of distributed power generation system that can further utilize waste heat for heating and cooling. This will result in 60-90% of energy utilization efficiency. Micro Gas Turbine is one of attractive prime movers that can reduce environmental pollution, less maintenance, and flexible in fuel supply. However, environmental performance of MGT-TGS depends on the operation strategy employed. In order to reduce emission of CO2, NOx and CO, studied on optimum operation strategy based on environmental performance of MGT-TGS in residential building loads for tropical region was carried out. Two actual size of MGT, 30kW and 65kW were used as the prime mover, and equipment and configuration of MGT-TGS were designed to cover energy load of a residential building in tropical region. Emission reduction index was used to compare emissions of MGT-TGS with different operation strategies. Result shows that MGT with smaller capacity at higher operation load will produce least emissions. Thus, base load is the most optimum operation strategy in terms of environmental performance. Thus, the best solution is base load that used smaller MGT. However, economic performance also must be further studied because smaller MGT has higher cost per kW, and it has slightly lower power generation efficiency.